Perencanaan Jembatan Beton Prategang Dengan Bentang 24 Meter Berdasarkan Standar Nasional Indonesia (SNI) - Batubara, Samsuardi; Simatupang, Larno (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2018)
Bridge is used to connect divided road sections, which are seperated by obstacles such as deep valley, river, lake, irigation canals, railway, and also grade seperated roadway. The construction of a bridge must comply with several requirements namely stiffness, deflection, and load bearing requirement. This research is a structural analysis and design of prestressed concrete girder beam with 24m length and 6.5m width. Working loads are dead load (MS), additional dead load (MA), vehicle load (TD), braking load (TB), pedestrian load (TP), and wind load (EW). Internal forces are obtained using Finite Element Method in SAP2000 nonlinear. Design of the bridge structure follows the national standar SNI 1725:2016 and RSNI T-12-2004. Result of structural design and analysis of the prestressed concrete girder beam uses 4 prestressed beam (160cm height, 1.83m distance between beam), 20cm bridge slab, and diaphragm with the dimension of 20x165x125cm . The number of tendon used in the design is 3, and each tendon comprises of 12 strand. The amount of prestressed force caused by jacking is Pj=5351.30 kN with loss prestress 24.52%. Deflection caused on the prestressed beam is dmaks = 12.6 mm (<dijin =80 mm), and occuring stress is 8696 kPa (< allowed stress 18675 kPa).